Center for Dairy Research Annual Report 1987-1988 - Quinones, Sarah Hundt; Wendorff, Bill; Johnson, Mark; Olson, Norman F. (Center for Dairy Research, University of Wisconsin-Madison, 1988)
The Center for Dairy Research has grown substantially since its formation in 1986. It has administrative oversight of 34 research projects or programs funded by the Wisconsin Milk Marketing Board, National Dairy Promotion and Research Board, State of Wisconsin, University of Wisconsin, and private industry. Research areas encompass (l) Safety and quality of milk products (2) Cheese research, (3) Milk components and their uses. In the latter, milkfat modification and utilization receives greatest emphasis. The original concept of fostering multi-disciplinary research is being realized with projects underway in six academic departments including production, processing, and economics of milk and milk products. As we strive, step by step, to be a high caliber research center, we are frequently reminded of our dependence on feedback from the dairy producers and dairy foods processors which help us design effective applied and basic research projects. As we see it, to succeed in our goal of increasing the utilization of milk and milk products, the food industry and researchers must team up to produce products of appeal to the evermore demanding consumer. A prosperous dairy economy will depend upon the dialogue between researchers, marketers, and business people involved in this industry. A unique and rapidly evolving project within the Center is the Worldwide Information and Technology Exchange Program. Designed to bring together dairy research efforts and information, WITEP coordinates an annual conference, a seminar series, special conferences and workshops, a scientist exchange program, and the preparation of various published materials. We hope you find this report informative and a source of enthusiasm. We invite all segments of the dairy research effort - marketing and promotion boards, universities, individual researchers, and private industry - to help us move forward and join us in building the resources of scientific skills, communication networks, and innovative ideas in dairy research. This unified effort, I believe, is critical for the solid and dynamic growth of dairy research.
Keywords: milkfat research; dairy research; dairy product safety; cheese technology